Moral Work, Teaching Profession and Character Education in Forming Students’ Characters - Lonto, Apeles Lexi; Wua, Telly D.; Pangalila, Theodorus; Sendouw, Recky (International Journal of Engineering and Technology, 2018)
The purpose of this study was to determine the problems that occur in State Senior High School 9 Manado, where the way the teacher works has not shown maximum performance caused by a lack of awareness and discipline in carrying out duties as a professional teacher. Similarly, about the weakness in capturing students in the learning process. Objective research is to determine whether there are influence morale, the teaching profession and character education in shaping the character of the students at State Senior High School 9 Manado. The samples used were 45 and data analysis techniques by using Karl Pearson correlation product moment. Results of research on the relationship variables X and Y are the relationship working moral Influence, the teaching profession and character education in shaping the character of the students at State Senior High School 9 Manado classified as a solid relationship. To determine the magnitude of the power of determination is working right relationship influence, the teaching profession and character education in shaping the character of the students at State Senior High School 9 Manado result is 95%, and the remaining 5% is influenced by other factors not examined by the author. To test the significance of the formula t count by the rule of testing: the result is 8.834, and the equation t table is 1.671.Â t count > t table or 8.834> 1.671. In conclusion morale effect relationship, the teaching profession and character education n in shaping the character of the students at State Senior High School 9 Manado results are significant.